Assessing urban heat island in Jakarta, Indonesia during the pandemic of Covid-19. Issue 1 (1st February 2022) - Saputra, A; Ibrahim, M H; Shofirun, S; Saifuddin, A; Furoida, K
Abstract: Jakarta, the capital city of Indonesia, is the most populated area in Indonesia, with a population of 10.56 million people or around 3.91% of the total Indonesian population. Jakarta has also become an important city in Indonesia as around 80% of Indonesian economic activity is located in this area. No doubt, the urban activity caused the air pollution to infuriate its microclimate, including the urban heat island phenomena. During the Covid-19 pandemic, Indonesia applied the partial lockdown for several areas to decrease virus transmission. Most of the transportation and commercial areas were closed, and most people worked from home. This significant shifting will affect the temperature and urban heat island conditions. Thus, the main objective of this research was to analyse the urban heat island during the early stage of the pandemic in Jakarta. We used Landsat 8 imagery to extract the land surface temperature (LST) and generated the urban heat island (UHI). The correlation was used to determine the relationship between the distribution of covid-19 cases with the UHI distribution. From the four different recording times (May, July, September, and December 2020) of Landsat 8 imagery, the highest UHI, 7.76°C was found in December 2020 (the late first year of the pandemic). The lowest UHI, 4.91°C was found in May 2020 (The early stage of the first year). Furthermore, the UHI hot spot moved from almost evenly in East Jakarta in May 2020, a tiny spot in East Jakarta in July and September 2020, and evenly distributed in Southeast Jakarta in December 2020. In addition, we found that the increase of covid-19 cases had a positive correlation with the UHI in Jakarta, which means the areas with the high UHI value have high new covid-19 cases. These results showed that the area with high activities is very prone to covid-19 transmission.